2021
DOI: 10.1071/hc21036
|View full text |Cite
|
Sign up to set email alerts
|

Employing nurse practitioners in general practice: an exploratory survey of the perspectives of managers

Abstract: INTRODUCTIONEstablishing the nurse practitioner (NP) workforce in New Zealand is a viable solution to health and workforce challenges in primary health care. General practices have been slow to implement NP services. Managers of general practices are central to the employment and development of NP roles. AIMTo explore the perspectives of managers on employing NPs in general practice. METHODSAn electronic survey was used to collect demographic and numerical data, which were analysed descriptively and analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…One such initiative aimed to foster inter-professional cooperation within the same geographical area is the establishment of territorial healthcare communities, and our study reflected this since the GPs actively participating in these communities were more likely to perceive APNs as beneficial for both themselves and their patients. This is in line with the results of a study conducted in New Zealand, that shows that managers of general practices working with nurse practitioners (which could be more likely in broader healthcare communities) had a more positive perceptions of their role [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…One such initiative aimed to foster inter-professional cooperation within the same geographical area is the establishment of territorial healthcare communities, and our study reflected this since the GPs actively participating in these communities were more likely to perceive APNs as beneficial for both themselves and their patients. This is in line with the results of a study conducted in New Zealand, that shows that managers of general practices working with nurse practitioners (which could be more likely in broader healthcare communities) had a more positive perceptions of their role [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, nurses are getting more and more involved in primary care (e.g. home environments, general practices) to deal with the increasing number of people with chronic diseases and support them in living autonomously for as long as possible (Mustafa et al, 2021). Because Flanders is currently undertaking a reorganisation of primary care, this context is a relevant opportunity to expand knowledge on how people with chronic conditions and their informal caregivers experience primary care.…”
Section: What Does This Paper Contribute To the Wider Global Clinical...mentioning
confidence: 99%
“…Executive nurse leaders play a signifcant role in facilitating the implementation of APN in healthcare systems by identifying and advocating for organizational and national health policy reforms [14,15]. Various studies that exist on the perspectives of nurse leaders regarding the implantation of advanced practice nursing roles internationally have shown that nurse leaders can better evaluate the potential of ftting APN roles within their healthcare system and overcome potential barriers and challenges [16,17]. To the best of our knowledge, the perspectives of executive nurse leaders regarding the feasibility of implementing APN have not been investigated in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%